The Effect of Workload and Transformational Leadership towards nurse performance in Islamic Hospital Ibnu Sina Pekanbaru - Muhammad Sayuti Alfatih Hadi Hadi; Raden Lestari Garnasih; Fiona Fiona (Westscience Press, 2026)
This study aims to examine the effect of workload and transformational leadership on nurse performance at Islamic Hospital Ibnu Sina Pekanbaru. The research population consisted of all 63 nurses, selected using non-probability and purposive sampling techniques. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS Version 23. The results show that workload significantly influences nurse performance, indicating that task demands and staffing conditions shape the ability of nurses to deliver optimal care. Transformational leadership also demonstrates a significant effect on nurse performance, highlighting the importance of supportive, motivational, and visionary leadership practices in strengthening work effectiveness and improving overall service quality within the hospital.